Marine thraustochytrid: exploration from taxonomic challenges to biotechnological applications - Wang, Qiuzhen; Zhang, Yong; Hui, Ruixue; Zhu, Yuanxiang (Frontiers in Marine Science, 2024)
Thraustochytrids, as a distinct group of heterotrophic protists, have garnered considerable attention owing to their remarkable adaptability in extreme marine environments, pronounced capacity for metabolic regulation and prolific production of high-value metabolites. The taxonomic classification of these microorganisms presents a substantial challenge due to the variability in morphological characteristics under different culture conditions. And this undermines the efficacy of traditional classification systems on physiological and biochemical traits. The establishment of a polyphasic taxonomic system integrating genomic characteristics in the future will provide new avenues for more accurate classification and identification. Thraustochytrids can effectively accumulate bioactive substances such as docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA), squalene and carotenoids. Through fermentation optimization and genetic modification, scientists have significantly enhanced the production of these metabolites. Moreover, the application of thraustochytrids in aquaculture, poultry and livestock feed has significantly improved animal growth and physiological indicators meanwhile increasing their DHA content. Natural bioactive substances in thraustochytrids, such as terpenoid compounds with antioxidant properties, have been proposed for application in the cosmetics industry. In the field of pharmacology, thraustochytrids have shown certain anti-inflammatory and anti-cancer activities and provide potential for the development of new oral vaccines. Additionally, they can degrade various industrial and agricultural wastes for growth and fatty acid production, demonstrating their potential in environmental bioremediation. Therefore, thraustochytrids not only exhibit tremendous application potential in the field of biotechnology, but also hold significant value in environmental protection and commercialization.